Pengaruh Sanksi, Razia Lapangan, dan Samsat Keliling terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor di Kabupaten Sumbawa - Mifta, Miftahul Jannah (EKALAYA : Jurnal Ekonomi Akuntansi, 2023)
This study aims to determine the effect of sanctions, field raids, and Mobile Samsat on Motor Vehicle tax compliance in Sumbawa regency. This type of research is quantitative. The data in this study uses primary data, the primary data was obtained from distributing questionnaires which were carried out directly using paper. The population in the studywas 67,152 people who were studied, only 100 respondents with the sampling method using the slovin method. Collecting data in this study by distributing questionnaires. The data analysis using the SPSS 26 program. The results of this study state that tax sanction have a significant effect on taxpayer compliance in Sumbawa Regency, field raids have no significant effect on taxepayercompliance in Sumbawa Regency, and mobile Samsat does not have a significant effect on taxpayer compliance in Sumbawa Regency